Penguatan Kapasitas Keluarga Melalui Edukasi dan Pendampingan Dalam Mengatasi Kecanduan Game Online Pada Anak di Kelurahan Pulokerto Palembang - Isyanawulan, Gita; Arianti, Yosi; Putri, Lisya Septiani; Hapsari, Yuanita Dwi; Ilham, Ilal; Muslimah, Hayana; Aziz, Muhammad Fakhri (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to enhance the understanding and capacity of families in Pulokerto Subdistrict, Palembang City, regarding the dangers of online game addiction among children, while training them to implement effective prevention and intervention strategies. The program was conducted using a participatory educational approach and intensive mentoring. Evaluation instruments included pre-test and post-test questionnaires, observation sheets, as well as guidelines for focus group discussions (FGDs) and interviews. Data were analyzed using descriptive analysis, a paired t-test, and N-Gain calculations to measure program effectiveness. The results showed an improvement in parents’ understanding and awareness of the impacts of online game addiction on children, as well as the importance of digital parenting. The average pre-test score increased from 87.72% to 94.36%, representing a gain of 6.64%, while the N-Gain score of 0.54 was categorized as moderate, indicating that the intervention was reasonably effective. In addition, the activity promoted collective parental awareness to implement consistent rules regarding gadget use, improve family supervision, and strengthen children’s social interactions within the family and community environment.